1997
DOI: 10.1597/1545-1569(1997)034<0135:amicwc>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Airway Management in Children with Craniofacial Anomalies

Abstract: Craniofacial anomalies (CFA) predispose children to airway obstruction. A retrospective study was conducted to describe airway intervention required to manage patients with craniofacial syndromes and diseases involving the midface and mandible (i.e., Pierre Robin, Apert, Treacher Collins, Saethre-Chotzen, CHARGE, Nager, Stickler, Goldenhar, and Pfeiffer). The type of airway intervention, duration of intervention, and associated physical and medical conditions were evaluated. One hundred nine patients had chart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 0 publications
2
62
1
Order By: Relevance
“…Therefore, when proper technique and protocol are followed, the validity of this method may be considered high. Most of the patients with craniofacial anomalies require airway management ranging from prone positioning to tracheotomy and DO 11 . DO is accepted as a reliable surgical technique and an alternative to tracheotomy for long-term management of the airway 11,12,13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when proper technique and protocol are followed, the validity of this method may be considered high. Most of the patients with craniofacial anomalies require airway management ranging from prone positioning to tracheotomy and DO 11 . DO is accepted as a reliable surgical technique and an alternative to tracheotomy for long-term management of the airway 11,12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients with craniofacial anomalies require airway management ranging from prone positioning to tracheotomy and DO 11 . DO is accepted as a reliable surgical technique and an alternative to tracheotomy for long-term management of the airway 11,12,13 . It has been observed that DO reduces the need for tracheotomy especially in pediatric patients and allows for early decannulation in patients who previously underwent tracheotomy 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…These patients may present chronic obstruction of upper airways -which leads to nourishment and sleep damages -as well as increasing hospital admissions. Frequent findings include micrognathia, tongue posture impairment, pharyngeal hypoplasia and laryngeal and tracheal narrowing, which result in respiratory obstruction and obstructive sleep apnea syndrome 6,10,12 . Computed tomography of rhinopharynx proved to be a useful diagnostic method to identify anatomical airway obstruction 13 , once it provides details of choanal atresia or other occasional malformation that are causative conditions to obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Transpalatal approach is preferred for older children and adults 14 . Advanced mandibular surgical procedure has been successfully described for improvement of respiratory obstruction in patients with retrognathia and upper airway narrowing 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation